Pressure injury prevention practice and associated factors among nurses at Wolaita Sodo University Teaching and Referral Hospital, South Ethiopia: a cross-sectional study. Issue 3 (14th March 2022) - Awoke, Nefsu; Tekalign, Tiwabwork; Arba, Aseb; Lenjebo, Tsegaye Lolaso
Abstract : Objective: The prevention of pressure injury is of great importance in providing quality care to patients, as it has been reported that approximately 95% of all pressure injury are preventable. Nurses working in clinical settings play a key role in identifying patients at risk and administering preventative care. Therefore, this study examines pressure injury prevention practices among nurses. Design: Cross-sectional study design. Setting: Wolaita Sodo University Teaching and Referral Hospital, Ethiopia. Participants: 240 nurses. Main outcome measures: Pressure injury prevention practices among nurses. Result: Among nurses, 37.9% had good pressure injury prevention practices. The factors associated with pressure injury prevention practices included having a bachelor's degree or higher (adjusted odds ratio (AOR)=2.18; 95% CI 1.12 to 4.25), having more than 10 years of nursing experience (AOR=3.44; 95% CI 1.41 to 8.37), lacking subject knowledge (AOR=0.49; 95% CI 0.27 to 0.91) and being over the age of 40 (AOR=0.55; 95% CI 0.09 to 0.35). Conclusion: The majority of nurses reported having a limited level of pressure injury prevention practice. Since pressure ulcer prevention practice is majorly the role of nurses. Upgrading the educational level of the nurses through continuous professional development opportunities can improve the preventive practice of pressure ulcer injury by increasing the knowledge and skill gained during the vocational training.